Formulation of Coniothyrium minitans for biocontrol of white mold caused by Sclerotinia sclerotiorum - Moretini, Alex; Melo, Itamar Soares de (Pesquisa Agropecuaria Brasileira, 2007)
Sclerotinia sclerotiorum, causal agent of white mold, maintains its resistant structures viable for many years in the soil, and its control is difficult. An alternative method for controlling it is the use of Coniothyrium minitans, an antagonistic fungus efficient in attacking the sclerotia. The objective of this work was to develop a method to encapsulate picnidia of C. minitans to control the white mold, using different polymers, such as alginate and pectin supplemented with wheat flour or cellulose and kaolin. Picnidia of C. minitans formulated in alginate 0.5%, cellulose 1.5%, and kaolin 5% survived better at 4 than at 28ºC when stored during two months. After this period, only the formulation stored at 4ºC maintained its viability. When the formulation was stored at 28ºC, the fungus lost its ability to grow after two months. The fungus formulated grew abundantly on the pellets when they were inoculated on PDA. They also reduced completely the disease incidence in infested soil.